2021
DOI: 10.3389/fonc.2021.679243
|View full text |Cite
|
Sign up to set email alerts
|

RuvBL1 Maintains Resistance to TRAIL-Induced Apoptosis by Suppressing c-Jun/AP-1 Activity in Non-Small Cell Lung Cancer

Abstract: Lung cancer is the common malignant tumor with the highest death rate in the world. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) as a potential anticancer agent induces selective apoptotic death of human cancer cells. Unfortunately, approximately half of lung cancer cell lines are intrinsically resistant to TRAIL-induced cell death. In this study, we identified RuvBL1 as a repressor of c-Jun/AP-1 activity, contributing to TRAIL resistance in lung cancer cells. Knocking down RuvBL1 effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…In our study, 5‐Fu treatment‐induced RUVBL1 upregulation, which was reversed by EIF3D silencing, implying the involvement of RUVBL1 upregulation in EIF3D‐caused 5‐Fu resistance, and this involvement was investigated through overexpressing RUVBL1. The study of Li has discovered that RUVBL1 maintains resistance to tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL)‐induced apoptosis in non‐small‐cell lung cancer 47 . Similar to this role of RUVBL1 in resistance to apoptosis, our results identified that RUVBL1 overexpression notably offsets EIF3D silencing‐caused potentiation on 5‐Fu‐induced viability decrease and apoptosis promotion.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In our study, 5‐Fu treatment‐induced RUVBL1 upregulation, which was reversed by EIF3D silencing, implying the involvement of RUVBL1 upregulation in EIF3D‐caused 5‐Fu resistance, and this involvement was investigated through overexpressing RUVBL1. The study of Li has discovered that RUVBL1 maintains resistance to tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL)‐induced apoptosis in non‐small‐cell lung cancer 47 . Similar to this role of RUVBL1 in resistance to apoptosis, our results identified that RUVBL1 overexpression notably offsets EIF3D silencing‐caused potentiation on 5‐Fu‐induced viability decrease and apoptosis promotion.…”
Section: Discussionsupporting
confidence: 78%
“…The study of Li has discovered that RUVBL1 maintains resistance to tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL)‐induced apoptosis in non‐small‐cell lung cancer. 47 Similar to this role of RUVBL1 in resistance to apoptosis, our results identified that RUVBL1 overexpression notably offsets EIF3D silencing‐caused potentiation on 5‐Fu‐induced viability decrease and apoptosis promotion. Besides, we observed that 5‐Fu treatment had no impact on eIF4E expression.…”
Section: Discussionsupporting
confidence: 78%
“…To our knowledge, less than 30 articles have checked the significance of NMP in NSCLC, and only four studies focused on HNRNPU or RUVBL1 [ 18 21 ]. All of these studies provided mechanistic evidence of the biological importance of HNRNPU or RUVBL1 in NSCLC in vitro models; however, only one investigated possible associations with patients’ survival in tumoral material [ 19 ]. No study approached this issue in clinical material based on protein levels.…”
Section: Introductionmentioning
confidence: 99%
“…RUVBL1, or RuvB-like AAA ATPase 1, has been associated with poor prognosis and a higher relapse rate in patients with diffuse large B-cell lymphoma (17). In addition, high expression of RuvBL1 in lung cancer was associated with a poor overall prognosis (18). NREP, or neuronal regeneration related protein, may be involved in neural function, including the promotion of axonal regeneration.…”
Section: Discussionmentioning
confidence: 99%